PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN MEDIA COUPLE CARD UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK SISWA KELAS IV SD IBS (ISLAMIC BILINGUAL SCIENCE) DARUL HIJRAH PUTRI - Rizki hidayah; Jumiati; Barsihanor (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2021)
The use of the lecture method has an impact on student activities and learning outcomes, it is necessary to apply a guided inquiry learning model with couple card media in Thematic learning. 3.2 and 4.2 in grade IV SD IBS (Islamic Bilingual Science) Darul Hijrah Putri. The purpose of this study was to determine the activities of teachers and students, as well as to determine the application of the guided inquiry learning model with the couple card media in improving student learning outcomes. The research method used is classroom action research (CAR). The subjects of this study were 19 fourth grade students of SD IBS (Islamic Bilingual Science) Darul Hijrah Putri. The research instrument used teacher activity sheets and student activity sheets and test questions. Data analysis used the percentage formula. The results of observations of teacher activities in the first cycle were 84.44%, in the second cycle 99.30%. Observation of student activity in the first cycle was 82.53%, the second cycle was 98.48%. The mastery of student learning outcomes has increased, the data before the action is 15.79%, then in the first cycle it is 94.74%, and the second cycle is 100%. Thus, the researcher can conclude that the application of the guided inquiry learning model with the couple card media on science material can improve the learning outcomes of fourth grade students of SD IBS (Islamic Bilingual Science) Darul Hijrah Putri.